Purchase Decisions of Local Cosmetic Products among Generation Z: The Role of Brand Awareness, Brand Trust, and Brand Attitude - Eva Syariefah Rachman; Dudi Amarullah; Nikita Astria; Aditya Sindu Sakti; Adysabzan T. Krois (Indonesian Journal Publisher, 2025)
The growth of the local cosmetics industry in Indonesia has shown significant growth in recent years, especially among Generation Z. This study aims to analyze the influence of brand awareness and brand trust on purchasing decisions for local cosmetic products, with brand attitude as a mediating variable. The research method uses a quantitative approach with an online survey of 164 Generation Z respondents who have purchased local cosmetics. Data analysis uses Structural Equation Modeling Partial Least Squares (SEM-PLS). The results show that brand awareness and brand trust have a significant positive effect on brand attitude. Brand attitude also has a significant effect on purchasing decisions. In addition, brand attitude is proven to mediate the influence of brand awareness and brand trust on purchasing decisions. These findings emphasize the importance of brand strengthening strategies to build positive consumer attitudes as a basis for forming purchasing decisions.